THE EFFECT OF AUDIT FOLLOW-UP AND SIZES ON THE AUDIT QUALITY - Mahpiansyah Mahpiansyah (Badan Pemeriksa Keuangan Republik Indonesia, 2016)
This study examines the effect of local audit size and the audit feedback implementation on audit quality in Indonesia. The Indonesian government has two audit institutions: external and internal audits. The audit feedback is a recommendation from the external audit to correct the audit subjects' financial reports. This study analyzes panel data of 33 provinces from 2009 to 2013 from Audit Report Badan Pemeriksa Keuangan (BPK) and Badan Pusat Statistik (BPS), using OLS and TSLS. There are two data variables: the number of data and the amount of data. Both dependent and independent variables contain the number of data and the amount of data except the audit size variables. Audit feedback is divided into finished audit feedback and unfinished audit feedback while audit sizes are divided into three variables. The study finds that audit feedback and audit size are statistically significant to influence the audit findings and the internal audit sizes based on the auditor's number, the number of the subject unit and the number of provincial employees are statistically significant only to the number of audit findings. It implies that the number of audit feedback affects the audit findings as a whole without being disturbed by the nominal amount of audit feedback. There are no previous studies that measure the effect of audit feedback on audit quality. This paper added an important question on the relationship between audit sizes and the effectiveness of audit feedback on audit quality in government institutions, especially in local governments. AbstrakPenelitian ini mengukur pengaruh ukuran audit dan tindak lanjut hasil audit terhadap kualitas audit di Indonesia. Pemerintah Indonesia memiliki dua institusi audit: eksternal dan internal audit. Tindak lanjut audit adalah perkembangan pelaksanaan rekomendasi audit dari audit eksternal untuk memperbaiki laporan keuangan auditee. Penelitian ini menganalisa data 33 provinsi dari tahun 2009 sampai dengan tahun 2013 dari Ikhtisar Laporan Hasil Pemeriksaan Badan Pemeriksa Keuangan (ILHP BPK) dan Daerah Dalam Angka Badan Pusat Statistik (DDA BPS) menggunakan OLS dan TSLS. Penelitian ini menemukan bahwa jumlah tindak lanjut hasil pemeriksaan dan ukuran audit berpengaruh signifikan terhadap temuan audit walaupun ukuran audit yang didasarkan pada jumlah internal auditor, jumlah unit subyek audit dan jumlah pegawai provinsi hanya berpengaruh signifikan terhadap jumlah temuan audit. Hal ini menunjukkan bahwa jumlah tindak lanjut audit secara keseluruhan mempengaruhi temuan audit tanpa terganggu dengan nominal tindak lanjut audit. Belum ada penelitian sebelumnya yang mengukur pengaruh dari tindak lanjut audit terhadap kualitas audit. Penelitian ini menambahkan pertanyaan penting mengenai hubungan antara ukuran audit dan efektivitas tindak lanjut audit pada kualitas audit di institusi pemerintah khususnya pemerintah daerah.